The Regularity of Stochastic Convolution Driven by Tempered Fractional Brownian Motion and Its Application to Mean-Field Stochastic Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, some properties of a stochastic convolution drivenby tempered fractional Brownian motion are obtained. Based on this result,we get the existence and uniqueness of stochastic mean-field equation drivenby tempered fractional Brownian motion. Furthermore, combining with theBanach fixed point theorem and the properties of Mittag-Leffler functions, westudy the existence and uniqueness of mild solution for a kind of time fractional mean-field stochastic differential equation driven by tempered fractionalBrownian motion.